Elaboração de protocolo para edição de imagens utilizadas na manufatura aditiva em cirurgia e traumatologia bucomaxilofacial - Costa, Mário César Furtado da (2018)
The use of virtual planning and impression of biomodels allows the improvement of the results of the surgical procedures of Buccomaxillofacial Surgery and Traumatology. This work methodology seeks to investigate errors in the planning and execution of the surgery, providing satisfactory functional and aesthetic results for the patient. This work created a virtual planning protocol associated to the use of the Additive Manufacturing, with the purpose of facilitating the management of the surgical procedures using the free software InVesalius, Blender and Meshlab. Thus, a step-by-step protocol for the creation and editing of images in STL format, acquired through DICOM images from tomographs, is presented, allowing surgeons to perform their surgical planning and allow the respective biomodels to be printed. This feature makes healthcare professionals accessible to 3D image processing and modeling for use in Additive Manufacturing.